Drosophila TRPA1 channel mediates chemical avoidance in gustatory receptor neurons - Kim, Sang Hoon (National Academy of Sciences, 2010)
Mammalian sweet, bitter, and umami taste is mediated by a single transduction pathway that includes a phospholipase C (PLC)β and one cation channel, TRPM5. However, in insects such as the fruit fly, Drosophila melanogaster, it is unclear whether different tastants, such as bitter compounds, are sensed in gustatory receptor neurons (GRNs) through one or multiple ion channels, as the cation channels required in insect GRNs are unknown. Here, we set out to explore additional sensory roles for the Drosophila TRPA1 channel, which was known to function in thermosensation. We found that TRPA1 was expressed in GRNs that respond to aversive compounds. Elimination of TRPA1 had no impact on the responses to nearly all bitter compounds tested, including caffeine, quinine, and strychnine. Rather, we found that TRPA1 was required in a subset of avoidance GRNs for the behavioral and electrophysiological responses to aristolochic acid. TRPA1 did not appear to be activated or inhibited directly by aristolochic acid. We found that elimination of the same PLC that leads to activation of TRPA1 in thermosensory neurons was also required in the TRPA1-expressing GRNs for avoiding aristolochic acid. Given that mammalian TRPA1 is required for responding to noxious chemicals, many of which cause pain and injury, our analysis underscores the evolutionarily conserved role for TRPA1 channels in chemical avoidance.